Is the education of local children influenced by living nearby a refugee camp? Evidence from host communities in Rwanda - Özge Bilgili; Sonja Fransen; Craig Loschmann; Melissa Siegel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper studies to what extent and in what ways access to educational services and schooling outcomes of local children are influenced by the presence of a refugee camp in or around their community. Taking the case of Congolese refugees in Rwanda and relying on household survey data collected in 2016, we investigate the availability of schools, schooling rates and access to school-based feeding programs in communities closer to and further away from three refugee camps: Gihembe, Kiziba and Kigeme. Furthermore, we conduct a cohort analysis to compare the years of schooling and primary school completion of Rwandans residing at different distances from each of these camps. Finally, on the basis of focus group discussions conducted among locals, we provide further insights into the ways in which locals perceive the effects of the refugee camp's presence on their children's access to schooling and educational outcomes. Our results highlight that living nearby a refugee camp does not have a negative influence on the education of local children. On the contrary, children residing closer to the camps have better schooling outcomes, and locals residing closer to the camps have a wide array of mostly positive views regarding the effects of refugees on local education. These results contribute to the body of literature on the effects of refugees on host communities and inform policies on how refugees need not be a "burden" if long-term investments are made and the voice of the locals are heard to address their needs.
Keywords: F22; I21; I31; R23; 330; Refugees; impact of refugees; host communities; education; Rwanda; Democratic Republic of Congo (DRC)